Consumption of Ultra-Processed Food and Cognitive Decline among Older Adults With Type-2 Diabetes. Issue 1 (19th March 2022) - Weinstein, Galit; Vered, Shiraz; Ivancovsky-Wajcman, Dana; Ravona-Springer, Ramit; Heymann, Anthony; Zelber-Sagi, Shira; Shahar, Danit Rivka; Beeri, Michal Schnaider
Abstract: Background: Ultra-processed food (UPF) consumption is related to increased morbidity and mortality. However, knowledge on its association with cognitive function is lacking. In this longitudinal study, we examined the associations between UPF intake and cognitive decline in older adults with type-2 diabetes (T2D). Methods: The sample included initially nondemented T2D older adults (≥65 years), from the Israel Diabetes and Cognitive Decline study, who had complete information on nutrition at baseline and at least 3 cognitive assessments (mean follow-up 5.3 ± 1.5 years). Nutritional intake was evaluated by a validated Food-Frequency Questionnaire, and foods were categorized as UPF based on NOVA classification. Percent of calories from UPF were calculated from total caloric consumption in total and specific food groups. Mixed effect models were used to examine the link between UPF intake (top vs bottom quartiles) and change in cognitive function overall and in specific domains, adjusting for potential confounders. Results: Of the total sample ( N = 568; mean age 71.3 ± 4.5 years, 60% men), 141 consumed >31% kcal from UPF (top quartile). Greater intake of ultra-processed meat was associated with a faster decline in executive functions and global cognition (β = −0.041 ± 0.013; p = .002 and β = −0.026 ± 0.010; p = .011, respectively). Additionally, consumption of ultra-processed oils/spreads was associated with faster decline in executive functions and global cognition (β = −0.037 ± 0.014; p = .006 and β = −0.028 ± 0.010; p = .009, respectively). Total UPF consumption and UPF-derived from dairy products and bread/pastries/starch were not associated with cognitive change. Conclusion: This study suggests that a high intake of ultra-processed meat and oils/spreads may be associated with accelerated cognitive decline in older individuals with T2D.